Incorrigíveis: teatro, festa e carnaval em uma poética pícara - Campos, Alysson Lemos (2020)
This dissertation aims to look at the creation processes of the street theater collective Os Pícaros Incorrigíveis (Fortaleza/CE), exploring the possible developments of a pícara poetic. The main research landscape is the spectacle “Devorando Heróis: a tragédia segundo os pícaros“ (2017), being configured as a fertile space for the elaboration of the collective's thoughts, which are imbued with the party and the carnival, elements that configure a conceptual framework that crosses the pícaras relationships, including from its aesthetic propositions to the ways of living together. Recognizing that it is a poetics that is supported by a liminal boundary between life and the theater, which the members propose to conceive from a carnivalized worldview. The methodological paths taken also assume a pícara nature, which, in dialogue with the Collective, feeds the discussion from the bar tables that the group usually inhabits, celebrating, drinking and devouring all the references that may interest in the elaboration of a poetics that, as well as the Pícaros, hold themselves incorrigible.